Harnessing Cu@Fe3O4 core shell nanostructure for biogas production from sewage sludge: Experimental study and microbial community shift. (April 2022) - Hassan, Gamal K.; Abdel-Karim, Ahmed; Al-Shemy, Mona T.; Rojas, Patricia; Sanz, Jose L.; Ismail, Sameh H.; Mohamed, Gehad G.; El-gohary, Fatma A.; Al-sayed, Aly
Abstract: Herein, we report a novel supplement called Cu@Fe3 O4 core shell nanostructure (NS) that revealed a tremendous increment in the biogas production from anaerobic digestion of sewage sludge. Cu@Fe3 O4 core-shell NS is synthesized using feasible co-precipitation method and characterized using different techniques before and after anaerobic digestion of sewage sludge. Five different concentrations (5, 10, 20, 40, and 80 mg/L) of Cu@Fe3 O4 core-shell NS was supplemented to separate bioreactors to study their effect on biogas production from anaerobic digestion of sewage sludge compared to Fe3 O4 nanoparticles alone. Microbial community assessed by next generation sequencing techniques has been used. The results showed a 3-fold increase in the biogas upon the use of moderate concentration (i.e., 20 mg/L) Cu@Fe3 O4 core-shell NS compared to using 40 mg/L of Fe3 O4 nanoparticles alone. There was a change in the microbial population after adding Cu@Fe3 O4 core-shell NS. The increase in the order of Clostridiales stands out, parallel to the decrease in Bacteroidetes . Regarding archaea, hydrogenotrophic pathway was the predominant, with partial replacement of Methanobrevibacter by Methanobacterium, while acetoclastic methanogen, especially Methanosaeta increased. Concisely, the deploying of the prepared Cu@Fe3 O4 core-shell NS not only resulted in enhancing the biogas production but also detoxified sewage sludge from hazardous materials.